Factors Influencing the Selection of Multimedia Engineering Expertise Competencies - Erlina Sukmawati; Rahmat Mulyono (PT Publikasiku Academic Solution, 2023)
Each Expertise Competency has its own enthusiasts, they have certain considerations before selecting a skill competency. Likewise with students who choose the Multimedia Engineering Skills Competency. They also have special considerations. For students who wish to choose the Multimedia Engineering Skills Competency, they will consider their talents, interests, personality, motivation, aspirations, perceptions or views, and the job opportunities they will get after graduating later by looking at the needs of the world of work and the number competitors, as well as encouragement from parents and peers for a job or for the Competency of Multimedia Engineering Skills itself. The considerations of each student are different from each other. This is because they have different talents, interests, personalities, motivations, aspirations and perceptions or views in assessing a Skills Competency, especially the Multimedia Engineering Skills Competency. Based on observations and field facts when carrying out activities at the Yogyakarta Vocational School, namely, the number of students who do not have basic talents and skills choose the Multimedia Engineering Skills Competency. In addition, some students complained in following the lesson. This is because they are forced to follow the wishes of their parents without considering the talents, interests, and basic skills possessed by students. In addition, there are some students who enter the wrong Skills Competency because of a lack of information about the Skills Competencies in SMKN 3 Yogyakarta. Of course this will make it difficult for students to follow the lesson and affect the motivation and achievement of student learning. The large number of student considerations in choosing a Skills Competency, made the writer interested in researching the effect of the interest of class X students choosing the Multimedia Engineering Skills Competency by taking the title The Influence of Interests of Class X Students in terms of Intrinsic and Extrinsic Factors on the Selection of Multimedia Engineering Skills Competency at SMKN 3 Yogyakarta . This study aims to determine the influence of class X students' interest in choosing the Multimedia Engineering Skills Competency, how much student interest is viewed from intrinsic factors and how much student interest is viewed from extrinsic factors. This research is an ex-post facto research with a quantitative approach. The population used is class X Multimedia Engineering Skills Competency at SMKN 3 Yogyakarta. Data collection uses questionnaires and documentation. Data analysis techniques using descriptive analysis techniques and multiple linear regression. The results of the study show that there is a positive and significant influence of the Intrinsic Factors and the Extrinsic Factors on the Selection of Multimedia Engineering Skills Competency. This is indicated by the correlation coefficient of 0.735, the determinant coefficient of 0.540, the effective contribution of intrinsic factors and extrinsic factors of 54%. The effective contribution of intrinsic factor is 4.8%. The interest of Class X students in terms of intrinsic factor is very high category as many as 8 students (22.9%), high category 19 students (54.3%), medium category 7 students (20%) and low category 1 student (2.9%). The data shows that the interest of class X students in Multimedia Engineering Skills Competency in terms of intrinsic factors is greatest in the high category. Then it can be explained from the intrinsic factors which include factors of willingness, pleasure, talent and motivation. Of these factors that give the biggest contribution is the factor of will. The interest of class X students in terms of extrinsic factors included 2 students (5.7%) in the very high category, 9 students (25.7%) in the high category, 19 students (54.3%) in the medium category, 4 students in the low category ( 11.4%) and very low category 1 student (2.9%). The data shows that the interest of class X students in Multimedia Engineering Skills Competency in terms of extrinsic factors is the largest in the medium category. Then it can be explained from extrinsic factors which include family and community environmental factors. Of these factors that give the biggest contribution is the family environment factor.